Studi Empiris Tentang Kinerja Guru dan Perilaku Kewargaan Organisasi Di Madrasah Negeri - Fradito, Aditia; Iqbal, Iqbal (Universitas Islam Negeri Raden Intan Lampung, 2024)
In the past few decades, there has been a significant amount of research on how the behavior of staff members can enhance organizational performance. This study investigates how organizational citizenship behavior impacts teacher performance in state madrasahs in Pesawaran Regency using a quantitative research design. Data was collected through a Google form distributed online to 222 randomly chosen individuals from the total population. The research had 148 respondents who completed questionnaires using a 5-point Likert scale. The collected data was analyzed using SPSS 25 software for Windows. The results indicate that organizational citizenship behavior has a positive and significant impact on the performance of state madrasah teachers, with a coefficient of determination of 0.493 (49.3%). This demonstrates that organizational citizenship behavior influences the performance of state madrasah teachers, while 50.7% of the performance is influenced by other unstudied factors. Furthermore, the organizational citizenship behavior variable's significance value of 0.000 is less than 0.05.